2014
DOI: 10.1158/0008-5472.can-13-2466
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fate Factor DACH1 Represses YB-1–Mediated Oncogenic Transcription and Translation

Abstract: The epithelial-mesenchymal transition (EMT) enhances cellular invasiveness and confers tumor cells with cancer stem cell like characteristics, through transcriptional and translational mechanisms. The mechanisms maintaining transcriptional and translational repression of EMT and cellular invasion are poorly understood. Herein, the cell fate-determination factor Dachshund (DACH1), suppressed EMT via repression of cytoplasmic translational induction of Snail by inactivating the Y box-binding protein (YB-1). In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 34 publications
1
76
0
Order By: Relevance
“…SUM159 cells were purchased from Asterand and authenticated by the supplier. MDA-MB-231 cells stably transfected with an inducible DACH1 plasmid were a gift from Dr. Richard G. Pestell (Thomas Jefferson University, Philadelphia, PA) (25). MCF-7 and SUM159 cells were transfected with empty pCMV6 (FLAG-tagged) vector or the same vector encoding for FoxQ1 using FuGENE 6.…”
Section: Methodsmentioning
confidence: 99%
“…SUM159 cells were purchased from Asterand and authenticated by the supplier. MDA-MB-231 cells stably transfected with an inducible DACH1 plasmid were a gift from Dr. Richard G. Pestell (Thomas Jefferson University, Philadelphia, PA) (25). MCF-7 and SUM159 cells were transfected with empty pCMV6 (FLAG-tagged) vector or the same vector encoding for FoxQ1 using FuGENE 6.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro protein-protein interactions were performed as described previously (24,25). In vitro translated proteins were prepared by coupled transcription-translation with a TNT-coupled reticulocyte lysate kit (Promega) using plasmid DNA (1.0 mg) in a total of 50 mL.…”
Section: Protein-protein Interaction By Gst Pull-down Assaysmentioning
confidence: 99%
“…Although it was reported that YB-1 initiates the capindependent translation of Snail mRNAs in breast cancer, 18,19 YB-1Yregulating Snail expression in other tumors including cervical cancer has not yet been investigated. Our experiment showed that the knockdown of endogenous YB-1 in cervical cancer cell lines decreased mRNA and protein levels of Snail but increased mRNA and protein levels of E-cad that is the direct transcriptional suppressive target of Snail and the hall marker of EMT, followed by the decreased invasive potential of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Wu et al 19 reported that DACH1 blocks YB-1Yinduced mammary tumor growth and EMT in mice via repression of cytoplasmic translation of Snail. However, the mode of YB-1 regulation of Snail in other tumors including cervical cancer still needs investigation.…”
mentioning
confidence: 99%